2018
DOI: 10.1007/s10120-018-00913-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes and prognostic factors with non-curative endoscopic submucosal dissection for gastric cancer in elderly patients aged ≥ 75 years

Abstract: Background Little is known about the long-term outcomes and prognostic factors with non-curative endoscopic submucosal dissection (ESD) in elderly patients with early gastric cancer. Methods Clinicopathological findings and long-term outcomes were evaluated in 87 patients with early gastric cancer (EGC) aged ≥ 75 years who were treated with non-curative ESD. Prognostic factors for overall survival (OS) were analyzed with the Kaplan-Meier method and a Cox proportional hazards model. Results During the follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 35 publications
(57 reference statements)
1
38
2
Order By: Relevance
“…Four objective indexes were identified in the search; PNI, CONUT, NRI and GNRI, of which 17 studies investigated PNI [43,46,50,[53][54][55][56][57][58][59][60][61][62][63][64][65][66], three GNRI [48,56,62], two CONUT [56,57] and two investigated NRI [36,68]. All but one study [68] investigated the use of objective indexes in surgical patients.…”
Section: Objective Indexesmentioning
confidence: 99%
“…Four objective indexes were identified in the search; PNI, CONUT, NRI and GNRI, of which 17 studies investigated PNI [43,46,50,[53][54][55][56][57][58][59][60][61][62][63][64][65][66], three GNRI [48,56,62], two CONUT [56,57] and two investigated NRI [36,68]. All but one study [68] investigated the use of objective indexes in surgical patients.…”
Section: Objective Indexesmentioning
confidence: 99%
“…A recent study identified the Charlson comorbidity index (CCI) as being a significant prognostic factor in elderly patients who underwent ER for SESCC. 78 In patients who underwent ESD for EGC, the American Society of Anesthesiologists Physical Status (ASA-PS), 99 CCI, 60,100 Eastern Cooperative Oncology Group Performance Status (ECOG-PS), 100 and prognostic nutritional index (PNI) 100,101 were identified as useful prognostic indicators; however, the attained results were not consistent across the studies, 32,60,[99][100][101] so more research is likely warranted. Furthermore, these commonly used unidimensional measures cannot fully do justice to the heterogeneity of elderly patients.…”
Section: Assessment Of Physical Condition In Elderly Patients With Eamentioning
confidence: 99%
“…This trend was more pronounced in elderly patients. 60 Therefore, among elderly individuals, the prognosis for those who underwent ER with curability C-2 may not be mainly associated with the gastric cancer.…”
Section: Prognosis In Patients Who Underwent Er With Curability C-2mentioning
confidence: 99%
“…80 In elderly patients with gastric cancer, it is necessary to evaluate not only the risk for LNM but also the condition of the patients because heterogeneity in the aging process leads to a diverse range of age-related declines in health and physical status among elderly patients. To date, several indices for evaluating the condition of patients, such as prognostic nutritional index, 81,82 Charlson comorbidity index, 81,83 and American Society of Anesthesiologists' Physical Status, 84,85 have been reported as indicators for the prognosis in patients with EGCs. However, some reports have shown conflicting results.…”
Section: Management After Noncurative Resectionmentioning
confidence: 99%
“…However, some reports have shown conflicting results. 81,[83][84][85][86] Therefore, for deciding treatment strategy in elderly patients with noncurative resection of ESD for EGCs, the establishment of a reliable tool for predicting the prognosis is demanded.…”
Section: Management After Noncurative Resectionmentioning
confidence: 99%